Highly active bile salt hydrolase from enterococcus faecalis shows positive cooperative kinetics - Chand, Deepak; Ramasamy, Sureshkumar; Suresh, C. G. (Process Biochemistry, 2016)
Bile salt hydrolase (BSH; cholylglycine hydrolase, EC 3.5.1.24) is an important enzyme that catalyses the deconjugation of bile acids conjugated with glycine or taurine and assists in the reduction of blood cholesterol levels. In the present study, we report the cloning, overexpression and characterisation of BSH gene from a gut-associated microbe Enterococcus faecalis (EfBSH). The overexpressed protein in Escherichia coli was purified to homogeneity. Optimum pH and temperature for activity were found to be 5.0 and 50 degrees C, respectively. The enzyme was considerably stable in the pH range of 5.0-7.0 and at a temperature of up to 50 degrees C. It showed high specific activity of 1390 U mg(-1) and 1289 U mg-1 for substrates such as glycocholic acid (GCA) and glycodeoxycholic acid (GDCA), respectively. The effect of additives on enzyme activity was assessed, and the detergent Triton X showed a marginally enhanced activity. The enzyme demonstrated unique enzyme kinetics of non-linear regression, thereby displaying positive cooperativity. In addition, the modulating effect of the non-substrate ligand Pen V on the hydrolysing ability of EfBSH towards bile acid such as GDCA was measured. It was observed that Pen V significantly enhanced the BSH activity. This is markedly different from the previously reported competitive inhibition of BSH activity by Pen V. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Allosteric regulation; Bile acids; Bile salt hydrolase; Enzyme kinetics; Gut organism; Penicillin V acylase